Enhancing doctoral learning through virtual communities of practice: an autoethnographic perspective - Huang, Hsin-Chi (Frontiers in Education, 2024)
This article explores the role of virtual communities of practice in enhancing the doctoral experience, particularly in the contemporary digital era. The author emphasizes the multifaceted benefits, including elevating academic networking, optimizing knowledge management, and supporting the mental wellbeing of remote learners. The establishment of clear shared objectives, dynamic leadership, and a conducive environment for collaborative innovation are identified as key prerequisites for building successful virtual communities of practice. As remote doctoral education becomes more prevalent, virtual communities of practice not only facilitate academic engagement but also foster mutual support and advocacy among doctoral students. The researcher, as a final year PhD student employed autoethnography as a research method to offer an intimate and reflective exploration of her personal experiences within virtual communities of practice. This unique insider perspective adds depth to the discussion on elevating academic networking, optimizing knowledge management, and supporting the mental well-being of remote learners. Furthermore, her ongoing doctoral research focuses on the socialization process and the development of a sense of belonging among doctoral students. Motivated by her research topics, she commenced her doctoral studies during the epidemic and cultivated the practice of consistently maintaining a researcher's reflection diary. The researcher utilized a thematic approach to thoroughly analyze the author's research diaries covering the period from December 2020 to August 2023. The article concludes by calling for further research into the professional identity development of doctoral students within virtual learning communities to achieve inclusive practices in the complex and diverse digital era of academia.